2020
DOI: 10.1534/genetics.119.302988
|View full text |Cite
|
Sign up to set email alerts
|

Parthenogenesis as a Solution to Hybrid Sterility: The Mechanistic Basis of Meiotic Distortions in Clonal and Sterile Hybrids

Abstract: Hybrid sterility is a hallmark of speciation, but the underlying molecular mechanisms remain poorly understood. Here, we report that speciation may regularly proceed through a stage at which gene flow is completely interrupted, but hybrid sterility occurs only in male hybrids whereas female hybrids reproduce asexually. We analysed gametogenic pathways in hybrids between the fish species Cobitiselongatoides and C. taenia and revealed that male hybrids were sterile owing to extensive asynapsis and crossover redu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(100 citation statements)
references
References 70 publications
11
89
0
Order By: Relevance
“…Previous studies have shown that the hybrid male’s sterility is caused by the inability to modify their gametogenesis in order to achieve clonality as females do. In this respect, males have problems with orthologous pairing in meiosis ( Kuroda et al 2019 ; Dedukh, Majtánová, et al 2020 ; Spangenberg et al 2017 ). Our analysis of gonadal microanatomy and flow cytometry did not indicate any aberration in male and female fertility, as both of them exhibited normal gonads with cells on various gametogenic stages.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the hybrid male’s sterility is caused by the inability to modify their gametogenesis in order to achieve clonality as females do. In this respect, males have problems with orthologous pairing in meiosis ( Kuroda et al 2019 ; Dedukh, Majtánová, et al 2020 ; Spangenberg et al 2017 ). Our analysis of gonadal microanatomy and flow cytometry did not indicate any aberration in male and female fertility, as both of them exhibited normal gonads with cells on various gametogenic stages.…”
Section: Discussionmentioning
confidence: 99%
“…inverted meiosis in butterflies [ 180 ]). Likewise, clonal gametogenic pathways, as premeiotic endoreplication, may also enable hybrids to successfully pass meiotic checkpoints [ 66 ] and to transmit at least parts of their genomes, despite the problems they experience with postzygotic incompatibilities [ 35 ]. Processes involving some type of hybrid-origin clonality allow the existence of hybrid vertebrates in the ‘extended speciation continuum’.…”
Section: The ‘Extended Speciation Continuum'mentioning
confidence: 99%
“…like in gynogenesis (middle), be truly fertilized, leading to ploidy elevation of offspring (left), or sperm may in part replace one of the maternal genomes in the egg, followed by its partial elimination (right) [ 54 ]. Gynogenesis (upper and lower rows): formation of clonal gametes by an ameiotic process (example: Poecilia formosa , upper row [ 47 , 64 ]; example: Carassius langsdorfii , lower row [ 65 ]) or endoreplication (example: diploid Cobitis elongatoides-taenia , upper row [ 66 , 67 ]; example: triploid Cobitis 1elongatoides-2taenia , lower row [ 66 68 ]) of genomes in germ cells followed by meiosis without effects of recombination. Diploid gametes (upper row) or triploid gametes (lower row) are fertilized without karyogamy, followed by sperm genome elimination.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, their fertility was differed by sexes: females are fertile but males are sterile (Pandian, 2010). Recently, Dedukh et al (2020) described this underlying mechanism in a study using C. taenia hybrids as follows:…”
Section: Introductionmentioning
confidence: 99%